Assembly of COPI and COPII vesicular coat proteins on membranes - Béthune, Julien; Wieland, Felix T. (Annual review of biophysics, 2018)
In eukaryotes, distinct transport vesicles functionally connect various intracellular compartments. These carriers mediate transport of membranes for the biogenesis and maintenance of organelles, secretion of cargo proteins and peptides, and uptake of cargo into the cell. Transport vesicles have distinct protein coats that assemble on a donor membrane where they can select cargo and curve the membrane to form a bud. A multitude of structural elements of coat proteins have been solved by X-ray crystallography. More recently, the architectures of the COPI and COPII coats were elucidated in context with their membrane by cryo-electron tomography. Here, we describe insights gained from the structures of these two coat lattices and discuss the resulting functional implications.
Gesehen am 15.08.2019